RIGHTS AND DUTIES OF THE INJURED PARTY IN CRIMINAL PROCEEDINGS - Petričević, Ana (Glasnik Advokatske komore Vojvodine, 2024)
In this paper, the author analyses the position of an injured party in criminal proceedings of the Republic of Serbia and underlines its rights and duties. The paper is divided into three parts. In the first part, the author examines the rights of a person who has been harmed by committing of a criminal offense, along with criticism of certain legal solutions and describing proposals in terms of de lege ferenda. The second part relates to the duties of the injured party in criminal proceedings, which are not particularly controversial. The last part includes the final considerations and suggestions aimed at improving position of the injured party in criminal proceedings by granting to it more rights than currently exist.